New and improved zero-knowledge argument systems for code-based cryptography - Tang, Khai Hanh (Nanyang Technological University, 2022)
Since a large amount of research devotes to improvements in quantum algorithms, current cryptographic constructions and primitives are at the threat of being broken once powerful quantum machines become real. Post-quantum cryptography appears to demonstrate cryptographic constructions and primitives believed to be secure against the attacks of such quantum machines. To this end, NIST proposed Post-Quantum Cryptography Standardization process to solicit, evaluate, and standardize quantum-resistant cryptographic algorithms. At the current stage of this process, many cryptographic algorithms in various assumptions against quantum-quantum computing advanced to the third-round submission. These quantum-resistant assumptions include code-based, lattice-based, multivariate and hash-based assumptions. Among these assumptions, code-based cryptography does not seem to get much attraction from the community of cryptographic research as many privacy-preserving systems are still missing or have not been improved much in terms of efficiency and diversity of functionalities.